Innovation of Tomato Pudding as a Supplementary Feeding (PMT) for a Nutritional Intervention Strategy to Prevent Stunting in Young Children in the Village of Babadan: Inovasi Pemberian Makanan Tambahan (PMT) Puding Tomat sebagai Strategi Intervensi Gizi untuk Mencegah Stunting pada Balita di Desa Babadan - Hayati, Anis Khoirin; Hidayah, Pratiwi Nur; Wulandari, Yunita; Amri, Rangga Nur Zaifatul; Hasan, Salma Tsaniyah El (Proceedings of The ICECRS, 2025)
Stunting, a prevalent health concern in Indonesia, particularly among children under five years of age, impedes children's physical growth and cognitive development.A nutritional intervention strategy to prevent stunting involves local food-based supplementary feeding (PMT). This community service program endeavors to develop and implement PMT innovations, specifically a tomato pudding fortified with vitamins A, C, and lycopene, as a balanced nutrition solution for toddlers in Babadan Village. The implementation method employed encompasses three stages: preparation, implementation, and reporting.The outcomes of the initiative demonstrated positive community acceptance and enhanced maternal awareness regarding the significance of nutrition in mitigating stunting.